Peningkatan Kesejahteraan bagi Kelompok Rentan melalui Pengolahan Briket: Praktik Baik Program Kang Ebit di Desa Kapu Kecamatan Merakurak Kabupaten Tuban : Improving Welfare for Vulnerable Groups through Briquette Processing: Good Practices of the Kang Ebit Program in Kapu Village, Merakurak District, Tuban Regency - Sukmayadevi, Sukmayadevi; Kinara, Lingga Gayuh; Trianto, Hasfin Bagus; Irawati, Shinta Tris (Civiliza Publishing, Indonesia., 2025)
Kapu Village, Merakurak District, is one of the highest agricultural producing areas and also has a high volume of local organic waste, such as palm fruit peels, coconut shells, and corn stalks, which are not yet optimally utilized. Pertamina Patra Niaga Fuel Terminal Tuban is present to provide a solution to this problem through the Kang Ebit (Eco-Briquette Village) Program. The purpose of this study was to examine the improvement in the social welfare of vulnerable groups through the empowerment efforts of the Kang Ebit Program implemented by Pertamina Patra Niaga Fuel Terminal Tuban. This research method used a qualitative approach, with informants from the community involved in the empowerment activities: 12 individuals from vulnerable groups in Kapu Village, who act as key actors in production and business management. The findings indicate that the Kang Ebit Program, involving these vulnerable groups, has created jobs, reduced regional unemployment, encouraged skills development, the growth of environmentally-based local entrepreneurs, and strengthened collective awareness of the importance of sustainable waste management. The implementation of the Kang Ebit Program has begun to show tangible impacts on the social, economic, and environmental aspects at the village level.